Tailored radical hysterectomy for locally advanced cervical cancer. Issue 8 (9th June 2020) - Sakuragi, Noriaki; Kaneuchi, Masanori; Kato, Tatsuya; Shimada, Chisa; Todo, Yukiharu; Ihira, Kei; Nozaki, Ayako; Umazume, Takeshi; Konno, Yosuke; Mitamura, Takashi; Kobayashi, Noriko; Murakami, Gen; et al.
Abstract : Objective: The survival and prognostic factors for locally advanced cervical cancer treated with nerve-sparing Okabayashi–Kobayashi radical hysterectomy have not been elucidated. We aimed to evaluate the oncological outcomes of those patients after radical hysterectomy with adjuvant chemotherapy. Methods: This retrospective cohort study was conducted from January 2002 to December 2011. Treatment was conducted at a single tertiary center in northern Japan. We used the Okabayashi–Kobayashi radical hysterectomy with lymphadenectomy. We applied unilateral nerve preservation for stage IIA/IIB cancer if there was a one-sided extension of the disease outside the cervix. Indication for adjuvant therapy was based on Sedlis criteria. High-risk was defined as evidence of lymph node metastasis, pathological parametrial invasion, and a positive/close surgical margin. The choice of adjuvant therapy was chemotherapy which consisted of paclitaxel and cisplatin. Results: The study included 76 early-stage IB1 (≤4 cm) and IIA1 cervical cancer and 45 locally advanced stage IB2 (>4 cm), IIA2, and IIB disease treated consecutively. The median follow-up was 106 (range: 6-203) months. There were 18 (15%) patients with recurrence, with five of 76 in the early-stage (7%) and 13 of 45 in the locally advanced disease (29%) (P<0.001). For locally advanced cervical cancer, pT classification (P<0.001), lymph node metastasis (P=0.007), and histology (P=0.05) were associated with locoregional recurrence. The five-year locoregional recurrence rate in the locally advanced disease was 20% and 5% in the early-stage disease (P=0.01). The five-year disease-free survival in the locally advanced cervical cancer was 71% and 93% in the early-stage disease (P<0.001). The overall survival in locally advanced disease depended on the adeno-type histology and lymph node metastasis. Conclusion: The tailored use of nerve-sparing Okabayashi–Kobayashi radical hysterectomy with adjuvant chemotherapy based on tumor histology and lymph node metastasis may be a possible option as a treatment of locally advanced cervical cancer in selected patients.